Photocatalytic Degradation of Deoxynivalenol Using Cerium Doped Titanium Dioxide under Ultraviolet Light Irradiation - He, Pengzhen (Toxins (Basel), 2021)
Deoxynivalenol (DON) is a major mycotoxin with high toxicity that often contaminates grains, foods and feeds. The traditional approaches for DON removal are difficult to meet industry and agriculture demands due to the high stability of the DON molecule. Therefore, there is an urgent need to develop green and effective strategies for DON degradation. In this study, a batch of photocatalytic nanomaterials of cerium (Ce) doped titanium dioxide (TiO(2)) were successfully prepared by sol-gel method. The catalysts were systematically characterized by XRD, HRTEM, FT-IR, UV-Vis and XPS. The catalyst 0.5Ce-TiO(2) showed superior photocatalytic activity for DON degradation in aqueous solution under ultraviolet light irradiation, better than that of traditional photocatalyst pure TiO(2), and 96% DON with initial concentration of 5.0 mg/L could be degraded in 4 h. In addition, the two possible degradation intermediate products C(5)H(8)O(3) and C(17)H(18)O(6) were identified, the photocatalytic degradation mechanism and degradation pathway were studied. The results indicate that Ce doped TiO(2) photocatalyst can be used to reduce DON effectively.